2004
DOI: 10.1007/s00198-004-1777-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of screws in normal and osteoporotic bone

Abstract: Fracture fixation in severe osteoporotic bone by means of implants that rely on screw anchorage is still a clinical problem. So far, a sufficiently accurate prediction of the holding capacity of screws as a function of local bone morphology has not been obtained. In this study the ultimate pullout loads of screws in the epi-, meta-, and diaphyseal regions of human tibiae were correlated to the cortical thicknesses and cancellous bone mineral densities at the screw axes determined from QCT densitometric data. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 16 publications
5
89
2
4
Order By: Relevance
“…The FE model was able to examine the effect of connection between the cortical shell and the screw, and conclude that even if the screw is not connected directly to the shell, the stiffening effect of the overlying layer can be important to pull-out force especially if augmentation material is present (Figure 7). This outcome is consistent with the work of others [39], and is of significance when dealing with methods of cement delivery and tests that follow because the delivery of cement to layers immediately underlying the cortical shell can be really effective in transferring load to the shell [41]. So as far as the cortex is concerned the adjacent cement increases its effective thickness and the contribution to pullout resistance.…”
Section: Discussionsupporting
confidence: 89%
“…The FE model was able to examine the effect of connection between the cortical shell and the screw, and conclude that even if the screw is not connected directly to the shell, the stiffening effect of the overlying layer can be important to pull-out force especially if augmentation material is present (Figure 7). This outcome is consistent with the work of others [39], and is of significance when dealing with methods of cement delivery and tests that follow because the delivery of cement to layers immediately underlying the cortical shell can be really effective in transferring load to the shell [41]. So as far as the cortex is concerned the adjacent cement increases its effective thickness and the contribution to pullout resistance.…”
Section: Discussionsupporting
confidence: 89%
“…BMD is an important determinant of the holding power of the pedicle screws in the vertebra [4,18,19]. Okuyama and coworkers [16] have shown that DEXA scan accurately assesses bone mineral density, which in turn influences biomechanical properties by determining, among many other factors, axial screw pullout strength.…”
Section: Discussionmentioning
confidence: 99%
“…With aging, several changes occur to the bone that change its biomechanical properties, making it more prone to fracture and more difficult to repair using standard techniques. The decreased cortical thickness and porosity combined with the loss of trabecular bone make it more difficult to obtain good purchase with standard fixation hardware [90]. Thus, when fixation is planned in osteoporotic bone, implants and constructs should be chosen that will maximize surface area contact with the remaining bone.…”
Section: Operative Fixation Of Fragility Fracturesmentioning
confidence: 99%